The influence of brown algae alginates on phenolic compounds capability of ultraviolet radiation absorption in vitro - Leonardo Tavares Salgado; Rodrigo Tomazetto; Leonardo Paes Cinelli; Marcos Farina; Gilberto Menezes Amado Filho (Brazilian Journal of Oceanography, 2007)
Brown algae phenolic compounds (PC) are secondary metabolites that participate in many biological processes, such as ultraviolet radiation (UV) protection, polyspermy blocking and trace metals bounding. Recently, PC has also been studied due to possible interactions with cell wall polysaccharides. However, there are few evidences of these interactions and their influence in physiological processes. The interactions between PC from the brown alga Padina gymnospora and alginates and the influence of these interactions on the UV absorption properties of PC were investigated in this work. Chromatography and spectrophotometry techniques were used to isolate, characterize and determine UV absorption capacity of studied compounds. Even after the P. gymnospora polysaccharide extraction and isolating methods, the PC was maintained linked to the alginate. The interaction of alginates with PC did not cause modifications on absorbance pattern of electromagnetic spectrum (UV-VIS-IR). The UV absorbance capability of PC linked to alginate was maintained for a longer period of time if compared with the purified PC. The obtained results reveal the strong linkage between PC and alginates and that these linkages preserve the UV absorption capability of PC along time. Os compostos fenólicos (PC) de algas pardas são metablitos secundários que participam de diversos processos biológicos, como proteção contra radiação ultravioleta (UV), bloqueio de poliespermia e ligação de metais. Recentemente, os PC têm sido estudados devido a possíveis interações com polissacarídeos da parede celular. Entretanto, existem poucas evidências sobre estas interações e sua influência em processos fisiológicos. Neste trabalho, foram investigadas as interações entre os PC de Padina gymnospora e os alginatos e a influência destas interações na capacidade de absorção de UV pelos PC. Foram utilizadas técnicas cromatográficas e espectrofotométricas para o isolamento, a caracterização e a determinação da capacidade de absorção de UV dos compostos estudados. Mesmo após a extração dos polissacarídeos de P. gymnospora e a utilização dos métodos de isolamento, os PC permaneceram ligados ao alginato. A interação de alginato com PC não causou modificações no padrão de absorção do espectro eletromagnético (UV-VIS-IR). A capacidade de absorção de UV dos PC ligados aos alginatos foi mantida por um tempo mais longo do que a do extrato de PC puros. Os resultados obtidos demonstram que há uma forte ligação entre PC e alginatos e que estas ligações preservam a capacidade de absorção de UV dos PC ao longo do tempo.